Robotic versus conventional laparoscopic gastrectomy for gastric cancer: A retrospective cohort study. (July 2018) - Liu, Hong-Bin; Wang, Wen-Jie; Li, Hong-Tao; Han, Xiao-Peng; Su, Lin; Wei, Deng-Wen; Cao, Ting-Bao; Yu, Jian-Ping; Jiao, Zuo-Yi
Abstract: Background: Robot-assisted gastrectomy (RAG), as an alternative minimally invasive surgical technique, is gradually being used for the treatment of gastric cancer (GC). This study aimed to assess the feasibility and safety of RAG over conventional Laparoscopy-assisted gastrectomy (LAG) for the treatment of GC. Methods: We retrospectively analyzed all procedures (RAG and LAG) performed by one surgeon between 31 January 2017 and 1 December 2017. The short-term of surgical outcomes were compared between two groups and further subgroup analyses were performed. Results: One hundred patients were enrolled in the RAG group and 135 in the LAG group. The demograghics and clinicopathologic characteristics are well matched between two groups. The RAG group had shorter postoperative hospital stay (11 (interquartile range 9–13) vs. 12 (10–14) day; p < 0.0001), earlier day of first flatus (2 (2–3) vs. 3 (2.3–3) day; p < 0.0001), and larger lymph nodes dissection (40.9 ± 13.1 vs. 35.4 ± 15.8; p = 0.004). Of interest, mean numbers of retrieved lymph nodes from station 6 (p = 0.002), 7 (p = 0.032), 10 (p = 0.025), 11p (p = 0.036), and 14v (p = 0.038) in RAG was significantly larger than LAG. However, no significant differences between two groups were observed in operative time (p = 0.136), operative blood loss (p = 0.434), days of eating liquid diet (p = 0.889), and postoperative complications (p = 0.752). In subgroup analyses, the similar results were observed. Conclusions: RAG for the treatment of GC is a safe and feasible procedure and beneficial for postoperative recovery of GC patients. However, further studies are needed to evaluate long-term and oncologic outcomes of RAG. Highlights: To compare the feasibility and safety of robot-assisted gastrectomy for gastric cancer versus conventional laparoscopy-assisted gastrectomy. Robot-assisted gastrectomy is a safe and feasible procedure and beneficial for postoperative recovery of gastric cancer patients. Robot-assisted gastrectomy has larger lymph nodes dissection from station 6, 7, 10, 11p, and 14v than laparoscopy-assisted gastrectomy.